Lesson Study as an Intervention to Develop Prospective English Language Teachers' Classroom Management Skills - Ertan Altınsoy (International Journal of Asian Education, 2021)
This study investigated six pre-service ELT teachers' engagement of collaborative Lesson Study, Japanese professional development model, and intended to explore its impact on their classroom management skills. The qualitative research design was used as the methodological foundation of the study since the Lesson Study experience of the participants was thoroughly observed in its natural context through research lesson applications. The large volume of data collected using a variety of data collection tools was analyzed using Atlas. Ti qualitative software. The study revealed that Lesson Study intervention impacted the participants' classroom management skills in various dimensions at varying degrees, especially in increasing awareness about the observation of student learning, giving instructions, and lesson planning aspects. The study further presented that Lesson Study provides a reformist professional development opportunity for pre-service teachers to practice various classroom management strategies in various actual classroom settings.